POLITICAL COMMUNICATION - Lee, Han Soo (The Oxford Handbook of South Korean Politics, 2021)
This chapter introduces political communication by focusing on electoral campaign communication. The evolution of campaign communication is associated with communication tools. Up until the 1997 presidential election, the main campaign method may be considered to have been mass rallies. The 1997 presidential election is considered the first TV election in South Korea. Since the 2002 presidential election, online communication tools have played a significant role in campaigning. Today, no candidate can win an election without using online communication tools in South Korea. Candidates mainly use online communication tools to mobilize voters, rather than to discuss policies. The influence of new media on South Korean voters is yet uncertain. The use of new media tends to positively affect political participation online, and online political participation is associated with offline political participation. However, the use of new media neither significantly nor consistently explains offline political participation and individual vote choice.
Keywords: mass media; media and politics; media campaign; new media; news media; online political campaign; political communication